INTESTINAL DYSFUNCTION IN RESPIRATORY INFECTION IN CHILDREN WHO ARE FREQUENTLY AND OCCASIONALLY ILL - Khiromon N. Sirojiddinova; Munira F. Usmanova (Central Asian Journal of Medicine, 2025)
The article reported 146 frequent children and 50 low-morbid children with intestinal dysfunction in respiratory infection. The RI manifestation of children with frequent illnesses is accompanied by a number of special and non-specific sipmtomas, as well as damage to several organs and systems. Children aged 1 to 3 (61%), children aged 3 to 4 (22.6%), and children aged 5 to 6 (10.9%) made up the bulk of the frequent cases. In some cases, this group was accompanied by a background of Ri intestinal dysfunction in children. This condition can be caused by incomplete development of normal microflora or frequent use of antibiotics.